Granulocyte colony-stimulating factor (filgrastim) in chemotherapy-induced febrile neutropenia - Advani S; Achreckar Suvarna; Thomas Dennis; Krishnankutty Binny (Indian Journal of Medical and Paediatric Oncology)
Background: The use of granulocyte colony-stimulating factors to treat patients with chemotherapy-induced neutropenia is well accepted. To assess whether administration of filgrastim along with standard empiric antibiotic therapy is beneficial for patients with chemotherapy-induced febrile neutropenia (FN), we conducted an open, non-randomized clinical trial. Materials and Methods: This was a prospective, open, Phase IV clinical trial in patients receiving chemotherapy for histologically confirmed cancer, with an oral temperature of >38.2°C and absolute neutrophil count (ANC) of <500/mm 3 . Filgrastim was administered subcutaneously in a dose of 5 mcg/kg/day, 24 hours after administration of cytotoxic therapy, for up to two weeks or until the ANC reached 10,000 cells/mm 3 . The parameters of assessment included duration of neutropenia, fever, hospitalization and antibiotic usage. Results: All 24 evaluable patients recovered from neutropenia, fever and FN in a median duration of two days. This result is similar to that reported in earlier studies with filgrastim. Despite the acceleration in recovery from neutropenia and fever, it also reduced the duration of hospital stay and usage of intravenous (IV) antibiotic. Only two adverse events were reported, which were of mild nature. Conclusion: Filgrastim, when used in patients with chemotherapy-induced neutropenia, exhibited efficacy in accelerating the recovery from neutropenia and fever comparable to that reported with filgrastim in literature. The data from this study suggest that filgrastim is effective in the treatment of chemotherapy-induced neutropenia and is well tolerated by Indian patients.